How to use a coagulation screen. Issue 1 (26th February 2021) - Kapur, Sarah; Gilmore, Mark; Macartney, Christine; Thompson, Andrew
Abstract : A coagulation screen is an important screening test when investigating a child who presents with easy bruising or bleeding. Interpretation of a coagulation screen can be challenging for clinicians. Evolution of the haemostasis system during childhood means normal ranges vary with age and needs to be interpreted alongside the clinical information. It is essential to consider preanalytical variables when interpreting a coagulation screen, and the reason for the investigation must always be considered. It is important that the sample is taken under optimal conditions, including sample technique, use of the correct bottle and prompt transport to the laboratory. An abnormal coagulation screen may indicate an underlying congenital bleeding disorder or an acquired bleeding disorder, or may be due to sampling error. Limitations of the coagulation screen are essential to be aware of, as some children with normal coagulation screen results may have bleeding disorders. Conversely, an abnormal coagulation screen does not always indicate a bleeding disorder.